CoPK32 is a novel stress-responsive protein kinase in the mushroom Coprinopsis cinerea - Kaneko, Keisuke; Sugiyama, Yasunori; Yamada, Yusuke; Sueyoshi, Noriyuki; Watanabe, Akira; Asada, Yasuhiko; Ishida, Atsuhiko; Kameshita, Isamu (Biochimica et biophysica acta, 2011)
In a previous study, we conducted an expression cloning screen of a cDNA library prepared from Coprinopsis cinerea mycelia using Multi-PK antibodies and detected a wide variety of Ser/Thr protein kinases. One of the isolated clones, CMZ032, was found to encode a putative Ser/Thr protein kinase designated CoPK32. In the present study, we investigated the biochemical properties and physiological significance of CoPK32. CoPK32 was expressed in Escherichia coli, and its biochemical properties were examined. The effects of high osmotic stresses on the growth of C. cinerea and on the endogenous CoPK32 activity in mycelia were also examined. CoPK32 showed autophosphorylation activity and effectively phosphorylated exogenous protein substrates. CoPK32S, a splice variant that was 18 amino acids shorter than CoPK32, showed much lower protein kinase activity than CoPK32. The catalytic properties of CoPK32 deletion mutants suggested that the C-terminal region of CoPK32 was important for the kinase activity and recognition of substrates. CoPK32 was highly expressed in the actively growing region of the mycelial colony. When mycelia were stimulated by high osmotic stresses, endogenous CoPK32 was markedly activated and the mycelial growth was severely inhibited. The activation of CoPK32 activity by high osmotic stresses was abrogated by SB202190 or SB239063 as well-known inhibitors of p38 mitogen-activated protein kinase. CoPK32 is involved in the stress response pathway in mycelia of C. cinerea in response to environmental stresses. In C. cinerea, protein kinases such as CoPK32 play important roles in signal transduction pathways involved in stress responses. ► CoPK32 is a MAPKAPK homologue in Coprinopsis cinerea. ► C-terminal region of CoPK32 is involved in substrate recognition. ► CoPK32 is predominantly expressed in actively growing mycelial colony. ► CoPK32 is significantly activated by high osmotic stress.